HUKUM ISLAM DANMUAMALAH (Asas-asas hukum Islam dalam bidang muamalah) - Abdul Munib (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
Islam is a religion serves as the rahmatal lil alamin,regulates the relation between khaliq and creatures. Islam comes as a regulator of relationships among human beings, such as buy and sells law, marriage, inheritance, etc., the goal is to get peace of people live, justice and love between eachother. The fundamental pinciple statement can be used as a guide of thought and action, arise principles from the results of research and action, the principle is permanent, general and every science has a principle that reflects the "essence" of the truth of the field of science. Principle is basic but it is not an absolute, the application means principles must take into specificaccount and changing circumstances. While muamalah means practice each other. In terms of muamalah divided in the narrow sense, is the rules of Allah swt that regulates human relationships with humans in an attempt to get the tools of his physical needs in a good way, in the broad sense muamalah is God Almighty that must be followed and obeyed in life of society to safeguard human interest in its affairs matters in wordsocial intercourse.